An Electron‐Rich Cyclic (Alkyl)(Amino)Carbene on Au(111), Ag(111), and Cu(111) Surfaces. Issue 32 (3rd June 2020) - Bakker, Anne; Freitag, Matthias; Kolodzeiski, Elena; Bellotti, Peter; Timmer, Alexander; Ren, Jindong; Schulze Lammers, Bertram; Moock, Daniel; Roesky, Herbert W.; Mönig, Harry; Amirjalayer, Saeed; Fuchs, Harald; et al.
Abstract: The structural properties and binding motif of a strongly σ‐electron‐donating N‐heterocyclic carbene have been investigated on different transition‐metal surfaces. The examined cyclic (alkyl)(amino)carbene (CAAC) was found to be mobile on surfaces, and molecular islands with short‐range order could be found at high coverage. A combination of scanning tunneling microscopy (STM), X‐ray photoelectron spectroscopy (XPS), and density functional theory (DFT) calculations highlights how CAACs bind to the surface, which is of tremendous importance to gain an understanding of heterogeneous catalysts bearing CAACs as ligands. Abstract : Served on a (golden) tray ! A highly reactive and electron‐rich (alkyl)(amino)carbene (CAAC) derivative was deposited on a surface, and its binding mode and ordering were investigated for the first time. Mobile CAAC‐Au species were found that form islands on the surface. These results open the door for more on‐surface studies of the highly relevant class of CAACs.